Phosphate selective binding and sensing by halogen bonding tripodal copper( ii ) metallo-receptors in aqueous media † - Bagha, H; Hein, R; Lim, JYC; Myers, WK; Sambrook, MR; Beer, PD (Royal Society of Chemistry, 2024)
Combining the potency of non-covalent halogen bonding (XB) with metal ion coordination, the synthesis and characterisation of a series of hydrophilic XB tripodal Cu(ii) metallo-receptors, strategically designed for tetrahedral anion guest binding and sensing in aqueous media is described. The reported metallo-hosts contain a tripodal C3-symmetric tris-iodotriazole XB donor anion recognition motif terminally functionalised with tri(ethylene glycol) and permethylated β-cyclodextrin functionalities to impart aqueous solubility. Optical UV-vis anion binding studies in combination with unprecedented quantitative EPR anion titration investigations reveal the XB Cu(ii) metallo-receptors exhibit strong and selective phosphate recognition over a range of other monocharged anionic species in competitive aqueous solution containing 40% water, notably outperforming a hydrogen bonding (HB) Cu(ii) metallo-receptor counterpart. Electrochemical studies demonstrate further the capability of the metallo-receptors to sense anions via significant cathodic perturbations of the respective Cu(ii)/Cu(i) redox couple.